Oil Price, Output and Employment in Turkey: Evidence from Vector Error Correction Model - Altay, Bulent; Topcu, Mert; Erdogan, Ebru (International Journal of Energy Economics and Policy, 2013)
This paper assesses the relationship among oil prices, real output growth and employment in Turkey over the period 2000:1-2012:4 by using vector error correction methodology. Empirical findings indicate a long-run relationship among the variables. Besides, short-run causality results based on vector error correction model provide an evidence of bi-directional causality linkage between oil prices and output, where uni-directional causality from oil prices and output to employment is established. The long-run causality analysis on the other hand shows that (i) the oil prices and real output do not cause employment, (ii) employment and real output do not cause oil prices, and however (iii) the oil price and employment cause output. Keywords: Oil price; output; employment; Turkish economy JEL Classifications: E24; Q43